Clinical gait characteristics in the early post-concussion phase: A systematic review. (January 2023) - Reidy, Joseph; Mobbs, Ralph; Kim, Jake; Brown, Eamon; Mobbs, Rowena
Highlights: Acutely following concussion, various gait alterations are seen which can correlate with degree of deficit and help guide prognosis. There are currently no reports in the literature that assess gait alteration in the seconds to minutes following concussion. Dynamic and postural assessments may identify more subtle gait deficits and therefore assist in more accurate diagnosis of concussion. Technology and standardised assessments should be used to recruit and analyse concussion patients in the future. Abstract: Background: Understanding gait alterations immediately post-concussion can improve identification, management and prognosis of concussion. Objective: To identify and define gait characteristics immediately post-concussion. Method: A review of electronic databases was conducted using terms gait alteration AND mTBI OR concussion. 172 reports were identified. After restricting to English and human studies, 158 remained. Reports were screened to include studies assessing quantifiable gait change post-concussion. 12 studies were included. Discussion: Multiple gait features are altered post-impact: stability, step length, walking speed and postural control. There is evidence that postural measures in gait initiation and termination may identify more subtle deficits. There is paucity of data evaluating the impact of concussion on gait function acutely and the authors identified no studies examining immediate changes. Conclusion: Acutely post-concussion, various gait alterations are seen and correlate with degree of deficit and prognosis. Slowed gait, instability and postural control are several features. Dynamic gait and postural assessments identify more subtle gait alterations. Given the absence in literature, high quality prospective studies examining immediate gait alterations post-concussion would contribute to improved assessment, management and prognostication. Given difficulty in participant recruitment, technological and standardised gait assessments should be used to assess force of impact and immediate gait alteration.